Reply to the Commentary on "Graphite and its hidden superconductivity" - P. Esquinazi (Papers in Physics, 2013)
A Reply to the Commentary by E. M. Forgan [Pap. Phys. 5, 050008 (20013)].Received: 30 October 2013, Accepted: 4 November 2013; Edited by: S. A. Grigera; DOI: http://dx.doi.org/10.4279/10.4279/PIP.050009Cite as: P. Esquinazi, Papers in Physics 5, 050009 (2013)